Women cancers in India: Incidence, trends and their clinical extent from the National Cancer Registry Programme. (October 2022) - Chaturvedi, Meesha; Sathishkumar, Krishnan; Lakshminarayana, Sudarshan Kondalli; Nath, Anita; Das, Priyanka; Mathur, Prashant
Abstract: Background: To provide a comprehensive assessment of women cancer in India utilizing the systematically collected data on all cancers by the National Cancer Registry Programme (NCRP). Methods: The study examined 10, 2287 cancer cases among women cancers providing cancer burden for major anatomical sites. Aggregated data of 28 PBCRs and 58 HBCRs under NCRP for 2012–16 was analysed for incidence rates, trends, cumulative risk of developing cancer, stage at detection and treatments offered. Results: Study results have found region –wide variation of women cancers by indicating highest proportions in western followed by southern region of India. North-Eastern region had lowest proportion. It was observed that breast is highest ranking cancer in most registry areas of urban agglomerations of country while cancer cervix was leading site in registries of rural areas like Barshi (15.3) and Osmanabad &Beed (13.1). States of Mizoram (23.2) and Tripura (9.5) along with Pasighat, Cachar and Nagaland. Median age of occurrence for women for these anatomical sites ranged from 45 to 60 years of age. For cancer breast, cervix and ovary –most cases were detected with regional spread. These findings were different for cancer corpus uteri where registries have reported higher proportions (49.3 %) of localized stage at detection. Loco regional cancers had higher proportions of multimodality treatments. Conclusion: Study provides a foundation for assessing the status of women cancers in the country. Variations between geographies would guide appropriate support for action to strengthen efforts to improve cancer prevention and control in underserved areas of the country. This would facilitate advocacy for better investments and research on women cancers. Highlights: Higher age specific rates with increasing age are observed for all female reproductive cancers. A significant decline in trend for cervical cancer was seen in registries. Increase in breast cancer incidence rates shows that rates have overtaken cancer cervix during 2000-03. Most of the cases of cancers of breast, cervix and ovary were detected at loco regional stage.